Morphology controllable synthesis of GdOF nanocrystals and application in theranostic purpose. (2022) - Mondal, Tanmoy; Haldar, Nibedita; Paul, Biplab; Kumar Ghosh, Chandan
Abstract: In this present paper, GdOF nanostructures have been synthesized by the urea based homogeneous coprecipitation method combining with high temperature (500 °C) calcination in presence of N2 . The nanostructures were structurally characterized by X-ray diffraction in conjunction with Rietveld refinements. The effects of pH of the reaction medium on the shape, size and morphology were explored and discussed in detail. The formation of GdOF nanostructures were represented with proper reaction mechanism elaborately. Vibrational energies of different bonds and defects states in our desired crystal structures were investigated using FTIR and Raman spectroscopy respectively. Under ultraviolet excitation, the GdOF nanomaterials show violet, blue and green emissions and get information about band edge energies. Based on its photoluminescence property, generation of reactive oxygen species (ROS) was investigated in detail.